Pengaruh Profesionalisme, Pengalaman, Akuntabilitas dan Objektivitas Auditor Terhadap Kualitas Audit (Studi Pada Kantor Akuntan Publik di Surabaya) - Mayta Ayu Wardhani; Made Dudy Satyawan (Nomicpedia: Journal of Economics and Business Innovation, 2021)
This research aims to obtain the effect of objectivity, epxperience, accountability also profesionalism on audit quality, the respondents of this research is auditors who work at Public Accounting Firms in Surabaya. The sample in this research is 70 auditors from 32 Public Accounting Firm in Surabaya. Analysis model in this research using multiple regression which state the relationship among variable independent and dependent variable assisted with SPSS 25, these research outcomes concluded that partially and simultaneously the objectivity, epxperience, accountability also profesionalism has significant affected on the quality of audit.